Real-world data on cabozantinib in advanced osteosarcoma and ewing sarcoma patients: a study from the Hellenic Group of Sarcoma and Rare Cancers - Kokkali, Stefania; Kyriazoglou, Anastasios; Mangou, Elpida; Economopoulou, Panagiota; Panousieris, Michail; Psyrri, Amanda; Ardavanis, Alexandros; Vassos, Nikolaos; Boukovinas, Ioannis (Journal of Clinical Medicine, 2023)
Advanced osteosarcomas (OSs) and Ewing sarcomas (ESs) tend to have poor prognosis with limited therapeutic options beyond first-line therapy. Aberrant angiogenesis and MET signaling play an important role in preclinical models. The anti-angiogenic drug cabozantinib was tested in a phase 2 trial of advanced OS and ES and was associated with clinical benefits. We retrospectively analyzed the off-label use of cabozantinib in adult patients with advanced OS and ES/primitive neuroectodermal tumors (PNETs) in three centers of the Hellenic Group of Sarcoma and Rare Cancers (HGSRC). Between April 2019 and January 2022, 16 patients started taking 60 mg of cabozantinib for advanced bone sarcoma or PNET. Median age at cabozantinib initiation was 31 years (17-83). All patients had received peri-operative chemotherapy for primary sarcoma and between 0 and 4 lines of treatment (median; 2.5) for advanced disease. The most common adverse effects included fatigue, anorexia, hypertransaminasemia, weight loss, and diarrhea. One toxic death was noted (cerebral hemorrhage). Dose reduction to 40 mg was required in 31.3% of the patients. No objective response was noted, and 9/16 patients exhibited stable disease outcomes. Progression-free survival varied from 1 to 8 (median; 5) months. Our study demonstrates that cabozantinib has antitumor activity in this population. In the real-life setting, we observed similar adverse events as in the CABONE study and in other neoplasms.